2-Methyl-versiquinazoline C, a new fumiquinazoline-type alkaloid from the fungus Aspergillus flavipes PJ03-11. Issue 6 (3rd June 2019) - Si, Ying-Ying; Tang, Ming-Xu; Lin, Shuang; Chen, Gang; Hua, Hui-Ming; Bai, Jiao; Wang, Yu-Bo; Wang, Hai-Feng; Pei, Yue-Hu
Abstract: A new fumiquinazoline-type alkaloid 2-methyl-versiquinazoline C (1 ), together with six known compounds (2–7 ), was isolated from Aspergillus flavipes PJ03-11 using OSMAC method. Their structures were elucidated on the basis of extensive spectroscopic analysis, and the absolute configuration of compound 1 was determined by the experimental and calculated ECD data. In addition, the cytotoxic activities against three human cancer cell lines (HL-60, THP-1, and PC-3) were evaluated. Abstract : UF0001